A study on information disclosure, trust, reducing search cost, and online group-buying intention. Issue 6 (10th October 2016) - Tseng, Shu-Mei; Lee, Meng-Chieh
Abstract : Purpose: More and more disputes have quickly emerged and accumulated, hence generating uncertainties and doubts among consumers regarding the online group-buying. In order to decrease such uncertainties, the purpose of this paper is to explore the relationships among information disclosure, trust, reducing search cost, and online group-buying intention, as well as proposing concrete suggestions for enhancing online group-buying intention. Design/methodology/approach: In order to explore the relationships among information disclosure, trust, reducing search cost, and online group-buying intention, the questionnaire and statistical analytical techniques were used. Moreover, as this study was an early attempt to develop a model for information disclosure, trust, reducing search cost, and online group-buying intention, partial least square therefore was appropriately to analyze data. Findings: The results showed that the level of information disclosure and trust on a group-buying website have positive influence on reducing search costs, while reducing search costs and trust have positive influences on online group-buying intention. Research limitations/implications: This research applied a purposive sampling method and obtained a slightly inadequate number of respondents. Therefore, it is suggested that future research should apply a random sampling method to collect more responses and increase the generalizability of the findings. Practical implications: By more actively disclosing information it is possible for group-buying websites to increase consumer trust and decrease search costs, thus enhancing their group-buying intentions. Originality/value: There are few studies on the relationships among reducing search cost, trust, and group-buying intention from the perspective of information disclosure. This study thus applies a questionnaire survey method to explore the relationships among them. This study also offers concrete suggestions to enhance group-buying intentions, and provides marketing strategies that can be used by online group-buying websites to raise their sales.